(3QSGdI aj JMbjb eYfi GdfXe hGdUjGZIs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3EYde Cf CSGS GdHdGZI hbGYOI GdaUGMI fXe GdcdGe dG HeYfi NJe HYVgG Edi HYV cja LGA hGJab Hd HeYfi JQJjHgG Ydi MSH JQJjH GdeYGfi s
(3BNQgG (B:s
(3hPdc HGdWQjbjf GdePchQjf dGf bhdg jHfi ai GdhLgjf GdePchQjf Ydi MbjbJg hGdJaGhJ GdePchQ ai GdOGdg aGage gPG GdSQ GdObjb s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B20s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdHdGZIs